First High-resolution Spectroscopy of X-Ray Absorption Lines in the Obscured State of NGC 5548 - Missagh Mehdipour; Gerard A. Kriss; Jelle S. Kaastra; Elisa Costantini; Liyi Gu; Hermine Landt; Junjie Mao; Daniele Rogantini (The Astrophysical Journal, 2024)
Multiwavelength spectroscopy of NGC 5548 revealed remarkable changes due to the presence of an obscuring wind from the accretion disk. This broadened our understanding of obscuration and outflows in active galactic nuclei. Swift monitoring of NGC 5548 shows that over the last 10 yr, the obscuration has gradually declined. This provides a valuable opportunity for analyses that have not been feasible before because of too much obscuration. The lowered obscuration, together with the high-energy spectral coverage of Chandra HETG, facilitates the first study of X-ray absorption lines in the obscured state. The comparison of the lines (Mg xi , Mg xii , Si xiii , and Si xiv ) between the new and historical spectra reveals interesting changes, most notably the He-like absorption being significantly diminished in 2022. Our study finds that the changes are caused by an increase in both the ionization parameter and the column density of the warm-absorber outflow in the obscured state. This is contrary to the shielding scenario that is evident in the appearance of the UV lines, where the inner obscuring wind shields outflows that are farther out, thus lowering their ionization. The X-ray absorption lines in the HETG spectra appear to be unaffected by the obscuration. The results suggest that the shielding is complex because various components of the ionized outflow are affected differently. We explore various possibilities for the variability behavior of the X-ray absorption lines and find that the orbital motion of a clumpy ionized outflow traversing our line of sight is the most likely explanation.